How Individuals May Benefit from the Experience of Emotions at Work? Evidence from a Double Moderating Model - Junça Silva, A.; Caetano, António; Lopes, M. (13th European Academy of Occupational Health Psychology Conference, 2018)
Purpose: Daily events are a constant in daily life at work, and can be divided into daily hassles and uplifts. Daily hassles are the tiny things that somehow irritate people. On the other hand, daily uplifts are considered as minor pleasures occurred in daily life. Both kind of events have been proved to influence individuals’ quality of work life. However, the role that emotion regulation strategies play on this relationship is unknown. Thus, this study intended to explore the role that emotion regulation strategies have on the link between daily hassles and uplifts, and workers’ subjective health. We hypothesized that emotion regulation strategies, in particular, supression and reappraisal, would moderate the link between daily hassles and subjective health. We also hypothesized that emotion regulation strategies would moderate the link between work-related daily uplifts and subjective health. Design: We collected data among 392 workers from diverse job sectors (60% female). Participants reported daily events occurred to them in the past week, strategies of emotion regulation used after those events, and perceptions of health. Results: Results show that the negative association between work-related daily hassles with health was influenced by an increased use of emotion suppression. Moreover, emotion reappraisal moderated the link unfriendliness customer daily hassles – health, such that the link was stronger when there was a low, and a moderate frequency of emotion reappraisal. Emotion regulation strategies did not moderate the link between daily uplifts and health. Limitations: The cross-sectional nature of the study, as well as, the self-reported nature of the data limits the generalization of our results. Practical Implications: This study contributes to the positive psychology literature by attempting to examine why daily events relates to individuals’ health. However, these results must be taken in light of our model analysis being conducted with cross-sectional data, which we discuss in further detail. Practical implications are further discussed. Originality: This empirical study advances practical knowledge on how to deal with daily events, and thus maximize the positive benefits of daily uplifts, and decrease the negative effects of daily hassles on perceived health.